In vitro analysis of integrin expression during chondrogenic differentiation of mesenchymal stem cells and chondrocytes upon dedifferentiation in cell culture - Gößler, Ulrich; Bieback, Karen; Bugert, Peter; Heller, Tobias Christian; Sadick, Haneen; Hörmann, Karl; Riedel, Frank (International journal of molecular medicine, 2006)
Tissue engineering represents a promising method for generating chondrogenic grafts for reconstructive surgery. In cultured chondrocytes, the dedifferentiation of cells seems unavoidable for multiplication. Stem cells, however, displaying unlimited self-renewal and the capacity to differentiate towards chondrocytes, might be usable after further characterization. As the interactions between the extracellular matrix and the cellular compartment can alter the cellular behaviour, we investigated the expression of integrins using microarray analysis during chondrogenic differentiation of human mesenchymal stem cells (MSC) in comparison with dedifferentiatiating human chondrocytes (HC) harvested during septoplasty. During chondrogenic differentiation of MSC, the fibronectin-receptor (Integrin β1α5), fibronectin and the GPIIb/IIIa-receptor were downregulated. The components of the vitronectin-receptor (Integrin αvβ3) and CD47 were constantly expressed and ILK was downregulated. Vitronectin and osteopontin were not expressed by the cells. In HC, Integrin β1α5 in conjunction with the ligand fibronectin were upregulated during dedifferentiation, Integrin αvβ3 as well as the GBIIb/IIIa-receptor were activated on day 21 but neither vitronectin nor osteopontin were expressed by the cells. The integrins, β2, β4, β6, β8 and α2, α4, α6, α7, α11, were not expressed at any time. ILK, CD47, and ICAP were activated with ongoing dedifferentiation. In conclusion, a candidate for signal-transmission is the fibronectin receptor (integrin α5β1) in conjunction with its ligand fibronectin. Other receptors, e.g. for vitronectin and osteopontin (αvβ3), or their ligands do not seem to be involved in signal transmission for dedifferentiation. The GPIIb/IIIa-receptor might assist the process of dedifferentiation. Intracellularly, ILK, ICAP1 and CD47 might be involved in the transduction of integrin-dependent signals.